2005
DOI: 10.1074/mcp.m500032-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Identification of Insulin-like Growth Factor-binding Protein-6 Induced by Sublethal H2O2 Stress from Human Diploid Fibroblasts

Abstract: Fibroblasts are the most ubiquitous cell types within our body. They produce various factors to maintain the texture and structure of a particular organ or tissue. To identify protein factors secreted by fibroblasts and alteration of these protein factors upon oxidative stress, HCA 3 human skin diploid fibroblasts were exposed to a sublethal dose of H 2 O 2 , which induces a prematurely senescent phenotype. Conditioned media from prematurely senescent cells versus control cells were analyzed for proteins using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 52 publications
1
31
0
1
Order By: Relevance
“…It is noteworthy that IGFBP-6 expression is increased by cellular stressors, including H 2 O 2 -induced oxidative stress (47). p38 activation has apparently contradictory effects.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that IGFBP-6 expression is increased by cellular stressors, including H 2 O 2 -induced oxidative stress (47). p38 activation has apparently contradictory effects.…”
Section: Discussionmentioning
confidence: 99%
“…However, several observations (Park et al, 2003;Guo et al, 2007) indicated that IGFBP-6 induction by TCDD is not mediated in the classical AhR and XRE-mediated way. In fact, evidence has been presented that IGFBP-6 induction is a general response to cell degeneration or injury in vitro and in vivo and unrelated to the mechanism of induction of AhR gene battery members (Xie et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The cell lysates used here do not contain secreted proteins, although microarray can detect genes encoding secreted proteins, for example MMP3 and IGFBP6. IGFBP6 was found elevated in H 2 O 2 treated HDFs while profiling the secreted proteins (Xie et al 2005). In addition to the absence of secreted proteins for proteomic detection, we used human 5 K cDNA gene chip for the microarray analyses in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Each sample was diluted by and dialyzed against 0.01 N NH 4 HCO 3 , passed through a 0.45-μm filter to remove insoluble cell debris, and concentrated down using a speed vacuum concentrator. After protein concentration determination by the Bradford method (Bio-Rad, Hercules, CA), protein mixtures from whole cell lysates were digested overnight with trypsin at a 50:1 ratio (Xie et al 2005). A microbore HPLC system (Paradigm MS4, Michrom, Auburn, CA) was used with two separation columns: a reverse phase (RP) column and a strong cation exchange (SCX) column (Whatman, Clifton, NJ).…”
Section: Methodsmentioning
confidence: 99%